Antiproliferative properties of clausine-B against cancer cell lines - Wan Mohamad Zain, Wan Nor I'zzah; Rahmat, Asmah; Othman, Fauziah; Yap, Taufiq Yun Hin (Penerbit Universiti Sains Malaysia, 2009)
Background: Clausine B, a carbazole alkaloid isolated from the stem bark of Clausena excavata, was investigated for its antiproliferative activities against five human cancer cell lines: HepG2 (hepatic cancer), MCF-7 (hormone-dependent breast cancer), MDA-MB-231 (non-hormone-dependent breast cancer), HeLa (cervical cancer), and CAOV3 (ovarian cancer).